THE EFFECTIVENESS OF WARM AND COLD COMPRESS TO REDUCE PERINEUM LASERATION PAIN AMONG POSTPARTUM PRIMIPARA IN BPM Y DEPOK 2019 - risza choirunissa (ITKM WIDYA CIPTA HUSADA, 2019)
Abstract Background: Every women who has undergone labor with a perineal wound will feel pain, pain that is felt by each postpartum women causes unpleasant effects such as pain and fear of moving, so non-pharmacological pain management is needed, namely with warm compresses and cold compress. Objective: This study was to determine the effectiveness of warm compresses and cold compresses on the intensity of perineal wound pain among post-partum womenin Yusrina Clinic Depok in 2019. Methodology: The design of this study used quasy experiment with the design of two groups of pretest and posttet design with the Mann Whitney test. This research was conducted in January-March 2019. The total sample were 30 people, 15 warm compress groups and 15 cold compress groups. The study population were post-partum women who had perineal injuries in Yusrina Clinic. The technique of warm compresses and cold compresses had done after 8 hours post-partum. The measuring instrument used was the Numerical Rating Scale (NRS). Results: The results of this study indicated that there was a difference between the treatment of warm compresses and cold compresses with a difference in the reduction of pain intensity with a value of p = 0.003 (p <0.05) after cold compresses was done while the value of p = 0.575 (p> 0.05) after warm compresses was done. p value 0.003 (p <0.05). Cold compress therapy was more effective in dealing with perineal wound pain in post-partum women compared to warm compress therapy. Conclusions and Suggestions: Compressive therapy is more effective in reducing the pain intensity of perineal lacerations in primipara postpartum women is cold compresses compared to warm compresses. This intervention can be applied in the practice of clinical midwifery care, especially in postpartum women as alternative therapy to treat perineal wound pain among post-partum women. Keywords: warm compresses, cold compresses, perineal wound pain